Exercise for people living with frailty and receiving haemodialysis: a mixed-methods randomised controlled feasibility study. Issue 11 (3rd November 2020) - Young, Hannah M L; March, Daniel S; Highton, Patrick J; Graham-Brown, Matthew P M; Churchward, Darren C; Grantham, Charlotte; Goodliffe, Samantha; Jones, William; Cheung, Mei-Mei; Greenwood, Sharlene A; Eborall, Helen C; Conroy, Simon; et al.
Abstract : Objectives: Frailty is highly prevalent in haemodialysis (HD) patients, leading to poor outcomes. This study aimed to determine whether a randomised controlled trial (RCT) of intradialytic exercise is feasible for frail HD patients, and explore how the intervention may be tailored to their needs. Design: Mixed-methods feasibility. Setting and participants: Prevalent adult HD patients of the CYCLE-HD trial with a Clinical Frailty Scale Score of 4–7 (vulnerable to severely frail) were eligible for the feasibility study. Interventions: Participants in the exercise group undertook 6 months of three times per week, progressive, moderate intensity intradialytic cycling (IDC). Outcomes: Primary outcomes were related to feasibility. Secondary outcomes were falls incidence measured from baseline to 1 year following intervention completion, and exercise capacity, physical function, physical activity and patient-reported outcomes measured at baseline and 6 months. Acceptability of trial procedures and the intervention were explored via diaries and interviews with n=25 frail HD patients who both participated in (n=13, 52%), and declined (n=12, 48%), the trial. Results: 124 (30%) patients were eligible, and of these 64 (52%) consented with 51 (80%) subsequently completing a baseline assessment. n=24 (71% male; 59±13 years) dialysed during shifts randomly assigned to exercise and n=27 (81% male; 65±11 years) shifts assigned to usual care. n=6 (12%) were lost to follow-up. The exercise group completed 74% of sessions. 27%–89% of secondary outcome data were missing. Frail HD patients outlined several ways to enhance trial procedures. Maintaining ability to undertake activities of daily living and social participation were outcomes of primary importance. Participants desired a varied exercise programme. Conclusions: A definitive RCT is feasible, however a comprehensive exercise programme may be more efficacious than IDC in this population. Trial registration numbers: ISRCTN11299707 ; ISRCTN12840463 .